Star Island [compact disc, unabridged] - Hiaasen, Carl (Random House Audio, 2010)
Twenty-two-year-old pop star Cherry Pye is attempting a comeback from her latest drug and alcohol disaster. Ann DeLusia is Cherry's "undercover stunt double", portraying Cherry whenever the singer is too wasted to go out in public. But, one night, Ann-as-Cherry is mistakenly kidnapped from a South Beach hotel by an obsessed paparazzo named Bang Abbott. Now the challenge for Cherry's handlers (uber-stage mother; horndog record producer; nipped-and-tucked twin publicists; weed-whacker-wielding bodyguard) is to rescue Ann while keeping her existence secret from the public and from Cherry herself.